Use of Extracellular Matrix Materials in Patients with Endocarditis - Sündermann, Simon Harald; Rodriguez Cetina Biefer, Héctor; Emmert, Maximilian Y.; Falk, Volkmar (The Thoracic and Cardiovascular Surgeon, 2014)
Tissue replacement is sometimes necessary during surgery for endocarditis. Commonly used materials are Dacron, expanded polytetrafluoroethlyene, or bovine pericardium. Those materials have no potential for bioresorption and cannot restore regional functionality. Extracellular matrices became available lately as patch material. Here we present two cases of patients with endocarditis. CorMatrix ECM (CorMatrix Cardiovascular, Inc., Atlanta, Georgia, United States) was used to repair intracardiac structures with good results in follow-up up to 3 months. CorMatrix ECM may be an adequate alternative to foreign material for patients with endocarditis.
Keywords: endocarditis; heart valve surgery; bioengineering